2003
DOI: 10.1007/s10350-004-6496-2
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Randomization Trial of Sequence Mass Screening for Colorectal Cancer

Abstract: Mass screening with a reverse passive hemagglutination fecal occult blood test along with an individual attributive degree value score was effective in reducing mortality from rectal cancer but not in reducing mortality from colon cancer or the incidence of colorectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
52
0
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 12 publications
0
52
0
3
Order By: Relevance
“…However because of its potential harm, acceptability [13] , availability, and expense [14] , the use of colonoscopy as a one-step screening method for the whole targeted population is unpractical in China. The use of noninvasive screening tests in primary screening, such as iFOBT and questionnaire investigation, have been adopted as the large scale population screening program in China [15] . The iFOBT and questionnaire investigation focused on different aspects.…”
Section: Discussionmentioning
confidence: 99%
“…However because of its potential harm, acceptability [13] , availability, and expense [14] , the use of colonoscopy as a one-step screening method for the whole targeted population is unpractical in China. The use of noninvasive screening tests in primary screening, such as iFOBT and questionnaire investigation, have been adopted as the large scale population screening program in China [15] . The iFOBT and questionnaire investigation focused on different aspects.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sample size is limited by the low colorectal cancer screening rate in the general population. Five randomized intervention studies demonstrated t h a t s c r e e n i n g c o u l d r e d u c e c o l o r e c t a l c a n c e r mortality [3][4][5][6][7] . However, screening rates in the general population are low.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence and mortality of colorectal cancer is increasing rapidly in developing countries [1,2] . Recently, strong evidence from several randomized intervention studies indicated that colorectal cancer screening is effective in reducing its mortality [3][4][5][6][7] . However, the reported compliance of colorectal cancer screening in the general population varies widely and is generally low.…”
Section: Introductionmentioning
confidence: 99%
“…In China, CRC is the fifth-leading cause of cancer mortality, with age-adjusted mortality rates of 5.29 and 3.86 per 100,000 for males and females, respectively (Zheng et al, 2003). Currently, the primary cause of CRC death relates to the development of distant metastases to organs, particularly to liver.…”
Section: Introductionmentioning
confidence: 99%